Care, Social Practices and Normativity. Inner Struggle versus Panglossian Rule-Following - Alexander Albert Jeuk (Rosenberg & Sellier, 2020)
Contrary to the popular assumption that linguistically mediated social practices constitute the normativity of action (Kiverstein and Rietveld, 2015; Rietveld, 2008a,b; Rietveld and Kiverstein, 2014), I argue that it is affective care for oneself and others that primarily constitutes this kind of normativity. I argue for my claim in two steps. First, using the method of cases I demonstrate that care accounts for the normativity of action, whereas social practices do not. Second, I show that a social practice account of the normativity of action has unwillingly authoritarian consequences in the sense that humans act only normatively if they follow social rules. I suggest that these authoritarian consequences are the result of an uncritical phenomenology of action and the fuzzy use of “normative”. Accounting for the normativity of action with care entails a realistic picture of the struggle between what one cares for and often repressive social rules.